The Role of the Relationship between Parents and Educators for Child Behaviour and Wellbeing - Pirchio, Sabine; Tritrini, Chiara; Passiatore, Ylenia; Taeschner, Traute (International Journal about Parents in Education, 2023)
Literature shows that family/school partnership leads to a better school experience (Marcon, 1999; Arnold et al., 2008, El Nokali, 2010, Powell et al., 2010). Building good relations is important especially during infancy. However, few studies examine the role of family-school partnership in early years. This study aims to investigate the quality of parent-teacher relation and its link with child’s behaviour and wellbeing. The research involved 193 families of children (12-42 months), attending 11 day-care centres, and 51 educators. Parents completed a questionnaire assessing their children’s temperament and psychological wellbeing, their own attitudes toward the day-care services, and the quality of parents/educators relationships. Educators filled in a questionnaire evaluating job satisfaction, children’s behaviour and quality of parent-educator relation. The frequency of parent-educator contacts, the parents’ perceived support, the educational value attributed to the day-care experience and the quality of the day-care entry are positively associated with the quality of parents-educators relationships. The parent-teacher involvement is positively associated with the child’s wellbeing, social orientation, emotionality and learning and with her day-care adjustment. The child’s behaviour improves along the school year, while no changes were found in the parents-educators partnership. Implications for future research and intervention in home-school relationship are discussed.